Efficacy and safety of ixabepilone plus capecitabine in elderly patients with anthracycline- and taxane-pretreated metastatic breast cancer - Vahdat, LT (2013)
Objectives: Data on chemotherapy regimens in elderly patients with metastatic breast cancer (MBC) are limited. The aim of this retrospective pooled analysis was to determine efficacy and safety of ixabepilone plus capecitabine versus capecitabine alone in patients with MBC aged ≥ 65 years. Materials and methods: A total of 1973 patients with MBC previously treated with or resistant to anthracyclines and taxanes were randomized in two open-label, multinational, phase 3 studies (study 046 and study 048). Patients received ixabepilone (40 mg/m(2) as a 3-hour intravenous infusion every 3 weeks) plus oral capecitabine (1000 mg/m(2) administered twice each day), or capecitabine alone (1250 mg/m(2) twice each day). Results: In total, 251 randomized patients were aged ≥ 65 years (ixabepilone plus capecitabine, n=116; capecitabine monotherapy, n=135). Efficacy results were consistent in patients aged <65 and ≥ 65 years with respect to the observed improvement in progression-free survival and objective response rate with ixabepilone plus capecitabine compared with capecitabine alone. No significant differences in overall survival between arms were observed for either subgroup. In the ixabepilone plus capecitabine arm, grade 3/4 hematologic adverse events (AEs) were similar in both subgroups except leukopenia and febrile neutropenia, which had a higher incidence in patients aged ≥ 65 years. The majority of grade 3/4 nonhematologic AEs were similar in the two subgroups, including fatigue, peripheral sensory neuropathy, and hand-foot syndrome. Conclusion: The combination of ixabepilone plus capecitabine maintains its efficacy in elderly patients with anthracycline and taxane pretreated MBC, with a similar safety profile to patients aged < 65 years.